Anodic benzylic C(sp3)–H amination: unified access to pyrrolidines and piperidines. Issue 14 (20th June 2018) - Herold, Sebastian; Bafaluy, Daniel; Muñiz, Kilian
Abstract : An electrochemical C–H amination process enables sustainable unified access to the heterocyclic classes of pyrrolidines and piperidines. Abstract : An electrochemical aliphatic C–H amination strategy was developed to access the important heterocyclic motifs of pyrrolidines and piperidines within a uniform reaction protocol. The mechanism of this unprecedented C–H amination strategy involves anodic C–H activation to generate a benzylic cation, which is efficiently trapped by a nitrogen nucleophile. The applicability of the process is demonstrated for 40 examples comprising both 5- and 6-membered ring formations.